Postural control under visual and proprioceptive perturbations during double and single limb stances: Insights for balance training - Hazime, Fuad A.; Allard, Paul; Ide, Maiza Ritomy; Siqueira, Cassio Marinho; Amorim, César Ferreira [UNESP]; Tanaka, Clarice (Elsevier, 2012)
Single Limb Stance under visual and proprioceptive disturbances is largely used in clinical settings in order to improve balance in a wide range of functional disabilities. However, the proper role of vision and proprioception in SLS is not completely understood. The objectives of this study were to test the hypotheses that when ankle proprioception is perturbed, the role of vision in postural control increases according to the difficulty of the standing task. And to test the effect of vision during postural adaptation after withdrawal of the somesthetic perturbation during double and single limb stance. Eleven males were submitted to double (DLS) and single limb (SLS) stances under conditions of normal or reduced vision, both with normal and perturbed proprioception. Center of pressure parameters were analyzed across conditions. Vision had a main effect in SLS, whereas proprioception perturbation showed effects only during DLS. Baseline stability was promptly achieved independently of visual input after proprioception reintegration. In conclusion, the role of vision increases in SLS. After proprioception reintegration, vision does not affect postural recovery. Balance training programs must take that into account. © 2011 Elsevier Ltd.
Keywords: Ankle; Balance control; Proprioception; Vibration; Vision; adult; ankle; body equilibrium; body movement; body posture; clinical article; evoked somatosensory response; human; limb movement; male; motor performance; oscillation; proprioceptive feedback; standing; task performance; velocity; vision; visual feedback; Adaptation, Physiological; Adult; Ankle Joint; Humans; Male; Physical Therapy Modalities; Postural Balance; Posture; Psychomotor Performance; Recovery of Function; Somatosensory Disorders; Vision, Low; Young Adult